2016
DOI: 10.1080/08952841.2016.1223968
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of back extensor strengthening exercises on quality of life in women with osteoporosis

Abstract: The aim of the present study was to evaluate the long-term effect of back extensor strengthening exercises on health-related quality of life (QOL) in women with osteoporosis. In this randomized clinical trial, 183 women with osteoporosis were treated with pharmacotherapy and weight-bearing and balance-training exercises. The case group additionally performed back extensor exercises at home. Patients filled out the Persian version of the Short Form (SF-36) QOL questionnaire at baseline and 6 months post treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results report a statistically significant increase in performance in the evaluation tools used, with superiority of the groups performing an exercise protocol ( Table 1 ) over the control groups [ 12 , 15 , 21 , 23 , 24 , 25 , 27 ].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The results report a statistically significant increase in performance in the evaluation tools used, with superiority of the groups performing an exercise protocol ( Table 1 ) over the control groups [ 12 , 15 , 21 , 23 , 24 , 25 , 27 ].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Furthermore, in a 2-year progressive resisted back strengthening exercise program among postmenopausal women in the study by Sinaki et al (10) demonstrated increased BEM strength and reduced bone loss and reduced incidence of vertebral fractures 8 years later in comparison to those without exercises. in the outcome measure (49). The other reason may be attributed to EQ5D VAS not been a sensitive tool to observe change in postmenopausal women with no osteoporotic fracture (50).…”
Section: Discussionmentioning
confidence: 99%
“…The exercise program in our RCT focused on strength training of the back extensor muscles and the legs, balance training, and weight-bearing exercises for the skeleton. This is also recommended in several studies, which have shown that physical training can improve balance and prevent falls and fractures, 6 , 27 , 28 , 29 , 30 , 31 , 32 improve health-related quality of life, 2 , 33 and decrease back pain. 32 Exercises that load the skeleton affect bone mineral density positively.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in back extensor strength has in previous studies shown to decrease problems with back pain and also to make daily activities easier. 1 , 2 , 3 It has also been shown that vertebral fractures can be prevented by activating and training back extensor muscles. 4 , 5 , 6 …”
mentioning
confidence: 99%